2016
DOI: 10.1155/2016/1937320
|View full text |Cite
|
Sign up to set email alerts
|

Ferritin Is a Marker of Inflammation rather than Iron Deficiency in Overweight and Obese People

Abstract: Background. In clinical practice, serum ferritin is used as a screening tool to detect iron deficiency. However, its reliability in obesity has been questioned. Objectives. To investigate the role of ferritin in overweight and obese people, either as a marker of inflammation or iron deficiency. Methods. On the basis of body mass index (BMI), 150 participants were divided into three equal groups: A: BMI 18.5–25 kg/m2, B: BMI 25–30 kg/m2, and C: BMI > 30 kg/m2. Serum iron, total iron binding capacity (TIBC), tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
63
3
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(75 citation statements)
references
References 27 publications
7
63
3
2
Order By: Relevance
“…In this study, 85% of obese subjects had CRP levels >3 mg/dL and 44% had levels >8 mg/dL, the former level representing subclinical inflammation and the latter clinical levels of inflammation . Other studies have reported similar direct correlations between BMI and higher CRP levels …”
Section: Obesity‐associated Modifications Of Iron Metabolismsupporting
confidence: 75%
“…In this study, 85% of obese subjects had CRP levels >3 mg/dL and 44% had levels >8 mg/dL, the former level representing subclinical inflammation and the latter clinical levels of inflammation . Other studies have reported similar direct correlations between BMI and higher CRP levels …”
Section: Obesity‐associated Modifications Of Iron Metabolismsupporting
confidence: 75%
“…Ferritin levels were also marginally modified by dietary intervention, with a significant reduction over time. As ferritin has been shown to be a marker of inflammation rather than iron deficiency in subjects with obesity [27], and ketosis has been widely proven to have an anti-inflammatory effect [28], we believe that this reduction parallels reduced systemic inflammation in our patients. However, no other inflammatory markers were assessed in this study, and we therefore cannot confirm this hypothesis.…”
Section: Discussionmentioning
confidence: 76%
“…Some other studies have analyzed correlation between hemoglobin and ferritin. Study by Khan et al showed that among overweight and obese people, ferritin had negative correlation with Hb, iron, TIBC, and transferrin saturation ( p < 0.001) [13]. Another study including pregnant women in third trimester showed that ferritin had weak correlation with hemoglobin (with Spearman coefficient of 0.21) [14].…”
Section: Discussionmentioning
confidence: 99%